Identification and Antioxidant Activity Test of Strawberry Ethanol Extract Rosalinda and Osogrande (Fragaria x Ananassa) Varieties - Enjelina, Ni Desak Gede Rista; Wijaya, I Nyoman; Suada, I Ketut; Phabiola, Trisna Agung; Utama, I Wayan Eka Karya; Yudha, I Kadek Wisma; Zhao, Tiejun (International Journal of Biosciences and Biotechnology, 2023)
Strawberries (Fragaria sp.) have many varieties spread across Indonesia. Pancasari Village, Buleleng is a strawberry producing area in Bali, there are several strawberry varieties cultivated by strawberry farmers in Bali, including the Rosalinda variety which has a sweet taste and the Osogrande has a sour taste. The purpose of this research is to determine the compounds contained in the fruits of these two varieties and to determine their antioxidant activity. Phytochemical analysis was performed using the GC-MS (Gas Chromatography-Mass Spectrometry) method, antioxidant activity was performed using the DPPH method. The results showed that the thick ethanol extract of (Fragaria x Ananassa) the Rosalinda and Osogrande varieties contained the same compound, namely 5-Hydroxymethylfurfural which has a function as an antioxidant, with 7 compounds that have known uses in the Rosalinda variety and 11 compounds in the Osogrande variety. The antioxidant activity of thick ethanol extract of the Rosalinda strawberry fruit is higher with IC50 of 10,05 ppm than the thick ethanol extract of Osogrande variety strawberry fruit with IC50 of 10,47 ppm, which means both are classified as having very strong antioxidant activity.